2020
DOI: 10.3390/app10238496
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Cleaning Processes and Their Influence on the Laser Resistance of Anti-Reflective Coatings

Abstract: Substrate cleaning prior to coating has a strong influence on the performance of the optical component. Exemplary, none or inadequate cleaning reduces the resistance against laser irradiation drastically. Especially in laser components coated with anti-reflective layers, the interface between substrate and coating is one of the most limiting factors. This study investigates different precision cleaning processes and their influence on the laser resistance of ion-beam sputtered anti-reflective coatings. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Additionally, an increase in laser energy triggers a more conspicuous thermally influenced region within the material. These discoveries harmonize with the observations documented by Gischkat et al, who highlighted substrate impairment beyond a particular threshold, wherein laser energy densities surpassing 15 J/cm 2 induce damage. Furthermore, elevated energy densities lead to more substantial impairment …”
Section: Resultssupporting
confidence: 87%
“…Additionally, an increase in laser energy triggers a more conspicuous thermally influenced region within the material. These discoveries harmonize with the observations documented by Gischkat et al, who highlighted substrate impairment beyond a particular threshold, wherein laser energy densities surpassing 15 J/cm 2 induce damage. Furthermore, elevated energy densities lead to more substantial impairment …”
Section: Resultssupporting
confidence: 87%
“…Initial studies showed that laser writing on filter paper was inefficient presumably because the white filter paper reflects most of the laser energy leading to low photothermal heating. 39 In the specimen at the left in Figure 4a, we repeated laser writing five times over the same area and observed the appearance of the red-colored "SCUT" pattern presumably due to the thermal decomposition of HAuCl 4 . For nanoparticle growth on the seeded filter paper, we placed the specimen in 1% HAuCl 4 solution containing hydroxylammonium chloride (0.2%), a reducing agent, for 30 min.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…As a control, we first wrote this pattern on filter paper (without GO), as illustrated at the left in Figure a. Initial studies showed that laser writing on filter paper was inefficient presumably because the white filter paper reflects most of the laser energy leading to low photothermal heating . In the specimen at the left in Figure a, we repeated laser writing five times over the same area and observed the appearance of the red-colored “SCUT” pattern presumably due to the thermal decomposition of HAuCl 4 .…”
Section: Resultsmentioning
confidence: 99%